Atypical Clinical Presentations of Acute Phase Chikungunya Virus Infection in Older Adults. Issue 11 (21st September 2017) - Godaert, Lidvine; Najioullah, Fatiha; Bartholet, Seendy; Colas, Sébastien; Yactayo, Sergio; Cabié, André; Fanon, Jean‐Luc; Césaire, Raymond; Dramé, Moustapha
Abstract : Objectives: We aimed to determine whether the presentation of Chikungunya virus (CHIKV) infection differs between older and younger adults with regard to clinical form during the acute phase defined by the World Health Organization: acute clinical, atypical, and severe acute. Design: Cross‐sectional, retrospective. Setting: University Hospital of Martinique. Participants: Individuals aged 65 and older (n = 267, mean age 80.4 ± 87.9) who attended the emergency department with a positive biological diagnosis of CHIKV (reverse transcriptase polymerase chain reaction) between January and December 2014 and a randomly selected sample of individuals younger than 65 (n = 109, mean age 46.2 ± 12.7). Results: Typical presentation was present in 8.2% of older adults and 59.6% of younger individuals ( P < .001), atypical presentation in 29.6% of older adults and 5.6% of younger individuals ( P < .001), and severe presentation in 19.5% of older adults and 17.4% of younger individuals ( P = .65). One hundred fourteen (42.7%) of the older group and 19 (17.4%) of the younger group could not be classified in any category (absence of fever, absence of joint pain, or both) ( P < .001). Conclusion: Only 8.2% of the older adults presenting in the acute phase of CHIKV have typical forms, suggesting that the most‐frequent clinical presentation of CHIKV in older adults differs from that in younger individuals. Abstract : See related article byLang et al .